Impact of agricultural residual plastic film on the growth and yield of drip-irrigated cotton in arid region of Xinjiang, China - Can, Hu; Wang, Xufeng; Wang, Shiguo; Lu, Bing; Guo, Wensong; Liu, Chaoji; Tang, Xiuying (International Journal of Agricultural and Biological Engineering, 2020)
Long-term and widespread use of plastic mulching has led to the accumulation of residual plastic film (RPF) in farmland soils of Xinjiang, China. However, there is no specific quantitative basis for RPF pollution or a clear understanding of the influence of residual film on crop growth. The aim of this study was to investigate the effect of RPF on the growth of cotton, an important cash crop of Xinjiang. Based on the field conditions and previous reports, various amount of residual film was applied in 0-30 cm soil layer. The growth index including emergence rate, dry matter, and yield of cotton was examined at different growth stages under different soil residual film levels. Results demonstrated a significant effect of RPF on soil moisture distribution and movement. Plastic residues had a significant effect on cotton growth at levels above 200 kg/hm2, and the yield decreased as the RPF amount increased. Based on these findings, 200 kg/hm2 was suggested as a threshold level to determine the effects of RPF on cotton. This study provided a basis to rate RPF pollution in farmland soils and help understand the impact of pollution on crop productivity. Keywords: residual plastic film, plastic film pollution, soil pollution, pollution control, cotton, production management DOI: 10.25165/j.ijabe.20201301.5084 Citation: Hu C, Wang X F, Wang S G, Lu B, Guo W S, Liu C J, et al. Impact of agricultural residual plastic film on the growth and yield of drip-irrigated cotton in arid region of Xinjiang, China. Int J Agric & Biol Eng, 2020; 13(1): 160–169.